Circulating Insulin-like Growth Factor-1 Levels in Patients with Rheumatoid Arthritis: A Meta-analysis - Zhao, Yu-Lan; Wu, Jun; Zhang, Tian-Ping; Cheng, Qian-Yao; Wang, Xue-Ping; Gu, Ming-Ming; Pan, Hai-Feng; Ye, Dong-Qing (Current Pharmaceutical Design, 2019)
Background and Objectives: Insulin-like growth factor-1 (IGF-1) levels have been investigated in rheumatoid arthritis (RA), however, produced inconsistent results. The purpose of this meta-analysis was to derive a more precise conclusion about serum/plasma IGF-1 levels in RA patients. Methods: PubMed, Embase and the Cochrane Library databases were searched up to December 2018 in English, and the studies comparing serum/plasma IGF-1 levels between RA group and healthy control group were what we are interested in. The Newcastle-Ottawa Scale (NOS) was used to assess the methodological quality of the included studies. The heterogeneity test was performed by the Cochrane Q statistic and I2 –statistic. The publication bias was evaluated by the funnel plot and Egger’s test. The standard mean difference (SMD) with 95% confidence interval (CI) was calculated by the fixed-effects or random-effects model. Results: A total of eleven articles with 334 cases and 261 controls were finally included. Compared with the healthy group, the RA group had lower circulating IGF-1 levels (pooled SMD= -0.936, 95% CI= -1.382 to -0.489, p<0.001). The subgroup analysis showed that RA patients from Asia (SMD= -0.645, 95% CI= -1.063 to -0.228, p= 0.002) and Europe (SMD= -1.131, 95% CI= -1.767 to -0.495, p<0.001) had lower circulating IGF-1 levels, no significant difference in plasma/serum IGF-1 levels was observed in RA patients from America. Sensitivity analysis indicated the stability and credibility of the overall effect sizes. Conclusion: Patients with RA have lower circulating IGF-1 level than healthy controls, particularly for patients from Asia and Europe. Further studies are necessary to elucidate the role of IGF-1 in the pathological process of RA.
Keywords: Cytokine